Analyzing transport properties of p-type Mg2Si–Mg2Sn solid solutions: optimization of thermoelectric performance and insight into the electronic band structure. Issue 3 (19th December 2018) - Kamila, Hasbuna; Sahu, Prashant; Sankhla, Aryan; Yasseri, Mohammad; Pham, Hoang-Ngan; Dasgupta, Titas; Mueller, Eckhard; de Boor, Johannes
Abstract : Figure of merit zT mapping of p-Mg2 Si1− x Sn x with respect to carrier concentration. Abstract : We have synthesized the complete stoichiometric range of p-Mg2 Si1− x Sn x, striving to optimize the thermoelectric properties of p-type Mg2 (Si, Sn) with respect to composition. The experimental data are analyzed in the framework of a single parabolic band (SPB) model and we can show that the thermoelectric properties can be well presented if acoustic phonon scattering and alloy scattering are taken into account. We find that the maximum achievable carrier concentration and power factor increase with higher Sn content. Also, the carrier mobility increases strongly from Mg2 Si to Mg2 Sn due to the changing density of states effective mass for the valence band which decreases from to . Retrieval of the acoustic phonon scattering potential ( E Def = 9 eV) and the alloy scattering parameter ( E AS = 0.5 eV) allows for modelling the thermoelectric properties for any arbitrary composition. Hence, we can predict the optimum zT for x ≈ 0.65–0.7 and the maximum power factor for Sn-rich compositions. Furthermore, we reveal that a significant improvement of the thermoelectric properties of Si-rich compositions can be achieved by increasing the carrier concentration experimentally and that the disparity between n- and p-type Mg2 (Si, Sn) is due to the differences between the valence and the conduction bands and not the interaction potentials.